1984
DOI: 10.1002/dvg.1020050304
|View full text |Cite
|
Sign up to set email alerts
|

Mating type differentiation in tetrahymena thermophila: Characterization of the delayed refeeding effect and its implications concerning intranuclear coordination

Abstract: Mating type determination in Tetrahymena thermophila involves developmentally programmed, heritable alterations of the macronucleus, localized to the rntd locus. This determination can be predictably controlled by the environmental conditions during macronuclear development, eg, temperature and time of refeeding. In this article we have further characterized the effects of delayed refeeding on mating type determination, as revealed by the frequency of mating types among the progeny of a cross. Our results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In order for them to evolve, this negative selective pressure must be counterbalanced by positive selection conferred either by the transposon itself or by the cellular process which produced and/or maintains them. The selective advantage of DNA rearrangement in the ciliates is not known, but it has been suggested that micronucleus-specific sequences act as negative regulatory sequences in the micronuclear genome of T. thermophila (15,37,57) or that variable DNA rearrangement might provide for genetic diversity (29,43,44) as it does for the mammalian immunoglobulin genes (50) and the trypanosome surface antigens (22).…”
Section: Discussionmentioning
confidence: 99%
“…In order for them to evolve, this negative selective pressure must be counterbalanced by positive selection conferred either by the transposon itself or by the cellular process which produced and/or maintains them. The selective advantage of DNA rearrangement in the ciliates is not known, but it has been suggested that micronucleus-specific sequences act as negative regulatory sequences in the micronuclear genome of T. thermophila (15,37,57) or that variable DNA rearrangement might provide for genetic diversity (29,43,44) as it does for the mammalian immunoglobulin genes (50) and the trypanosome surface antigens (22).…”
Section: Discussionmentioning
confidence: 99%
“…Because each new macronucleus (karyonide) is independently determined for mating type, mating type in T. thermophila is said to be karyonidal; macronuclei descended from each karyonide express the same mating type. Environmental factors, particularly temperature and nutritional state, influence the choice of mating type during macronuclear development (Nanney, Meyer, and Chen 1977; Nanney, Meyer, and Portnoy 1980; Orias and Baum 1984, 1985; Portnoy and Nanney 1980). The result is that the different mating types, designated I through VII, appear at different frequencies depending on the genotype and the environment.…”
mentioning
confidence: 99%
“…Also notice that regardless of the value of κ, there is no head-start effect when ω = 1 since all existing chromosomes have an equal probability of being selected. Aside from the extreme cases, various degrees of head-start mechanisms 30,33,39 can be achieved by some combinations of κ and ω. In general, the smaller the κ and larger the ω, the stronger the head-start becomes.…”
Section: The Model For Macronucleus Proliferationmentioning
confidence: 99%
“…At each of the pre-defined number of cell divisions, a sample of cells was taken from the clonal population, each of which was then cultivated separately to maturity to determine if it is pure for some mts. It should be noted that similar experiments focusing on either very early or late stages of growth of a clonal population were extensively conducted decades ago 32,[38][39][40] . A detailed diagram on the experimental procedure is given in the Methods section.…”
Section: The Experiments and Observationsmentioning
confidence: 99%
See 1 more Smart Citation